Quality of Life and Adjustment to Psychosocial Morbidity Among Adults Attending a Dermatology Clinic - Oke OO; Ariba AJ; Omisore AG (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: The skin is the largest organ in the body and has aesthetic significance. The presence of any skin lesion or skin disease might be associated with psychosocial morbidity and negative impact on the quality of life. Objectives: To determine the level and degree of adjustment to psychosocial morbidity associated with the presence of dermatological conditions and assessing the quality of life of affected adults. Methods: Data were collected from 189 new patients attending the Dermatology Clinic at the Federal Medical Centre, Abeokuta, Nigeria using systematic random sampling. The validated Adjustment to Chronic Skin (ACS) diseases questionnaire and Finlay's Dermatology Life Quality Index (DLQI) questionnaire were the research instruments. Results: The respondents consisted of 80 males (42.3%) and 109 females (57.7%) with a mean age of 36.3± 15.3 years. The least adjustment to skin-related psychosocial morbidity (49.7%) was observed with the helplessness scale. The mean score on the DQoL was 9.9 ± 6.2 and over half of the respondents (53.9%) reported moderate to an extremely large negative effect on their quality of life. Conclusion: The presence of dermatological conditions impact negatively on the quality of life and the least adjustment to skin-related psychosocial morbidity was experienced on the helplessness scale. Dermatology practitioners should acquire psychological evaluation and/or counselling skills to provide holistic care.